2022
DOI: 10.1002/nop2.1564
|View full text |Cite
|
Sign up to set email alerts
|

Learning engagement; nursing students' experiences in an online environment at a university

Abstract: Aim The aim of this study was to understand students' engagement with learning in an online environment at a university in Namibia. Design A qualitative descriptive design was applied. Methods Data were collected using in‐depth telephonic interviews among 12 purposively selected nursing students. Data were analysed thematically. Results While the students did practice engagement, their understanding of learning engagement was not clear. The students considered online learning to be a safe space for engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Participants said that WhatsApp, Moodle, Zoom and Google Meet's tools for instant chatting made it simple for students to be involved. This is consistent with the research, which found that internet‐based applications like Kahoot and Poll Everywhere increase students' involvement in the educational experience (Munangatire & Indjamba, 2023 ). The investigation further explained that instant messaging applications reduce barriers associated with anxiety, expand the pool of learners who can engage and boost their trust in their ability to do so.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants said that WhatsApp, Moodle, Zoom and Google Meet's tools for instant chatting made it simple for students to be involved. This is consistent with the research, which found that internet‐based applications like Kahoot and Poll Everywhere increase students' involvement in the educational experience (Munangatire & Indjamba, 2023 ). The investigation further explained that instant messaging applications reduce barriers associated with anxiety, expand the pool of learners who can engage and boost their trust in their ability to do so.…”
Section: Discussionsupporting
confidence: 92%
“…The breadth of learning, level of focus and self‐direction of learners may all be used to indicate their level of engagement. Engagement is more than just participating in educational tasks; it also involves emotional and mental variables (Munangatire & Indjamba, 2023 ). Thus, behavioural, affective and mental engagement are the three primary categories of engagement (Bowden et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Student engagement is influenced by several factors as has been identified in recent studies ( Dube & Mlotshwa, 2018 ; Ghalley & Rai 2019 ; Munangatire & Indjamba, 2023 ). According to Ghalley and Rai (2019) , these factors include age, gender, willingness to communicate, course level, student preparation, and emotions such as confidence or fear.…”
Section: Review Of Literaturementioning
confidence: 92%
“…According to Ghalley and Rai (2019) , these factors include age, gender, willingness to communicate, course level, student preparation, and emotions such as confidence or fear. Additional factors such as socioeconomic background, the ability to adapt to a new online learning environment, and low self-efficacy can also affect nursing students’ academic participation and performance ( Dube & Mlotshwa, 2018 ; Munangatire & Indjamba, 2023 ). Prior studies have also suggested that successful learning engagement is influenced by course design, peer pressure, confidence, and online teachers ( Koob et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%